Predictive Value of Transimpedance Matrix Measurements to Detect Electrode Tip Foldover. Issue 9 (30th October 2022) - Kay-Rivest, Emily; McMenomey, Sean O.; Jethanamest, Daniel; Shapiro, William H.; Friedmann, David R.; Waltzman, Susan B.; Roland, J. Thomas
Abstract : Objective: To evaluate the ability of the transimpedance matrix (TIM) measurement to detect cochlear implant electrode tip foldover by comparing results to a "gold standard, " the intraoperative plain film radiograph. Study Design: Retrospective case series. Setting: Tertiary referral hospital. Patients: One hundred three patients who underwent cochlear implantation between June 2020 and August 2021. Interventions: Intraoperative electrophysiologic monitoring (electrode impedances, neural response telemetry, and TIM measurement) and modified Stenver's view plain film radiographs. Main Outcome Measures: Identification of tip foldover on both TIM and plain films. Results: In total, 103 patients (117 ears) had both a TIM measurement and intraoperative X-ray available for review, including 68 adults and 35 children. One hundred patients (85%) received the Cochlear Slim Modiolar electrode. Tip foldovers were noted in three of 117 implants (2.5%). In all cases, TIM was able to detect the foldover, and the electrode arrays were reinserted with the patients still under anesthesia, with repeat X-ray demonstrating a normal configuration. Two other abnormal TIM patterns were identified. One was in a patient with an obstructed cochlea in whom only 10 electrodes could be inserted, the other was in a patient with a common cavity abnormality. One additional patient underwent electrode repositioning intraoperatively because of overinsertion. In this patient, the TIM appeared to be within normal limits, but the over-insertion was apparent on X-ray. Overall, the sensitivity and specificity of TIM measurements in detecting electrode tip foldover were both 100%. Conclusion: TIM measurements were able to accurately identify tip foldovers. More research is needed to define the adjunctive role of TIM as an intraoperative measure.